1983
DOI: 10.1073/pnas.80.14.4546
|View full text |Cite
|
Sign up to set email alerts
|

A primate model of parkinsonism: selective destruction of dopaminergic neurons in the pars compacta of the substantia nigra by N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine.

Abstract: A syndrome similar to idiopathic parkinsonism developed after intravenous self-administration of an illicit drug preparation in which N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (NMPTP) might have been responsible for the toxicity. In the present study we show that intravenous administration of NMPTP to the rhesus monkey produces a disorder like parkinsonism (akinesia, rigidity, postural tremor, flexed posture, eyelid closure, drooling) that is reversed by the administration of L-dopa. NMPTP treatment decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
650
0
9

Year Published

1986
1986
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,737 publications
(677 citation statements)
references
References 11 publications
13
650
0
9
Order By: Relevance
“…The dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [MPTP] is known to induce parkinsonism in hu-mans, primates, and mice ( [27,90,132,133]). MPTP is converted by astrocytes to the metabolite 1 methyl-4-phenylpyridinium [MPP + ], a substrate of the DA transporter ( [40,41]).…”
Section: Animal Models Of Parkinson's Diseasementioning
confidence: 99%
“…The dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [MPTP] is known to induce parkinsonism in hu-mans, primates, and mice ( [27,90,132,133]). MPTP is converted by astrocytes to the metabolite 1 methyl-4-phenylpyridinium [MPP + ], a substrate of the DA transporter ( [40,41]).…”
Section: Animal Models Of Parkinson's Diseasementioning
confidence: 99%
“…The cardinal clinical symptoms are bradykinesia, tremor, rigidity, and postural instability with the pathological characteristic of evolutional nigrostriatal dopaminergic neurodegeneration [2,3] . 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin that induces parkinsonism in both humans [4] and non-human primates [5] with the cognitive, biochemical, histological and classical behavioral changes that occur in PD [6] . Therefore, Increasing evidence has suggested that single photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging can be used to sensitively and objectively evaluate the integrity of the nigrostriatal dopaminergic system and may be useful tools for providing diagnostic information on PD [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Administration of MPTP to man or non-human primates (Davis et al 1979;Langston et al 1983;Burns et al 1983) including common marmosets (Jenner et al 1984) induces a selective destruction of dopaminergic nigrostriatal neurons associated with a substantial decrease in dopamine content of the caudate nucleus and putamen. MPTP is converted by monoamine oxidase type B (MAO-B) into the dihydropyridinium species (MPDP Ă·) which is converted non-enzymatically into the neurotoxic l-methyl-4-phenylpyridinium ion (MPP Ă·; Castagnoli et al 1985).…”
Section: Introductionmentioning
confidence: 99%